Effect of steam blanching on the quality of dried male (cocos nucifera L.) flowers for coconut tea production - Caranto, Kathleen Rose A.
This study was conducted to determine the effect of blanching used as pre-treatment to the quality of dried male Cocos nucifera flowers to be used for the production of coconut tea. Drying rate of flowers steam blanched for six minutes was calculated to be 0.88 g/min with a critical moisture content of 0.83. Dried flowers steam blanched for six minutes and then roasted were also found to have most acceptable sensory attributes as a coconut tea provided that decoction preparation for tea is used. Sorption Isotherm model for dried roasted male Cocos nucifera flowers was classified as type III. Sorption isotherm models such as BET, Henderson, Smith, Oswin and Bradley were used to predict isotherm of the product. BET equation was used to determine monolayer value of dried male Cocos nucifera flowers and it was calculated to be 0.022 g H2O/g dry matter. Oswin model was used to predict the sorption isotherm of the product. Results from this study can be used to predict the shelf-life as well as packaging requirements for coconut tea production.